High-thermal-conductivity electromagnetic shielding silica gel composite material and preparation method thereof
By adding MXene powder, h-BN material and nanographene powder to the silicone composite material, the problem of insufficient thermal conductivity and electromagnetic shielding of silicone materials is solved, significantly improving the thermal conductivity and electromagnetic shielding performance of the material, and meeting the high requirements of modern electronic equipment.
Patent Information
- Application Number
- CN202411877712.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-28
AI Technical Summary
The thermal conductivity of silicone materials is low and the electromagnetic radiation shielding effect is poor, making it difficult to meet the high requirements of modern electronic equipment for thermal conductivity and electromagnetic radiation shielding.
By adding MXene powder, h-BN material and nanographene powder to the silicone composite material, the high thermal conductivity, excellent electrical conductivity and electromagnetic shielding performance of these materials can be used to significantly improve the thermal conductivity and electromagnetic shielding performance of the composite material.
It significantly improves the thermal conductivity and electromagnetic shielding performance of silicone composite materials, can effectively block the transmission of electromagnetic waves, reduce leakage and interference of electromagnetic radiation, and provide strong guarantee for the stable operation of electronic equipment.
Smart Images

Figure CN119529537A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a high thermal conductivity electromagnetic shielding silica gel composite material and a preparation method thereof. Background Art
[0002] As a common thermal insulation material, silicone plays an important role in the application of electronic equipment. However, with the continuous enhancement of the functions of modern electronic equipment and the increasing complexity of the structure, the requirements for the thermal conductivity and electromagnetic shielding performance of the material are becoming higher and higher. In this context, the thermal conductivity and electromagnetic shielding performance of silicone have become the key factors limiting its further application.
[0003] First, regarding thermal conductivity, silicone has a relatively low thermal conductivity, which means it is not very efficient at transferring heat. In electronic devices, especially in high-density integrated components, the rapid transfer and effective dissipation of heat is essential to ensure the stable operation of the device. The poor thermal conductivity of silicone may cause heat to accumulate inside the device, which in turn affects the performance and life of the device;
[0004] Secondly, regarding electromagnetic shielding performance, the poor shielding effect of silicone is also an issue that needs attention. With the rapid development of wireless communication technology, electronic equipment will generate a large amount of electromagnetic radiation during operation. These radiations may not only interfere with the normal operation of the equipment, but also pose a potential threat to human health. Therefore, higher requirements are placed on the electromagnetic shielding performance of the material. However, the electromagnetic shielding ability of silicone is limited, and it is difficult to meet the effective control requirements of modern electronic equipment for electromagnetic radiation. For this reason, a high thermal conductivity electromagnetic shielding silicone composite material and a preparation method thereof are proposed. Summary of the invention
[0005] In view of this, the present invention hopes to provide a high thermal conductivity electromagnetic shielding silica gel composite material and a preparation method thereof, so as to solve or alleviate the technical problems existing in the prior art and at least provide a beneficial choice.
[0006] The technical solution of the embodiment of the present invention is implemented as follows: a high thermal conductivity electromagnetic shielding silica gel composite material, including the following raw materials in parts by weight: 15 to 20 parts of MXene powder, 45 to 60 parts of h-BN material, 0.5 to 2 parts of nanographene powder, 70 to 80 parts of silica gel, polyimide and polyetheretherketone blend, 3 to 8 parts of urea, 1 to 3 parts of plasticizer, 1 to 2 parts of stabilizer, and 1 to 2 parts of flame retardant. The MXene powder is a two-dimensional layered material derived from transition metal carbon / nitrogen / carbonitride, the h-BN material is composed of two elements of boron (B) and nitrogen (N), its chemical formula is BN, and its crystal structure is hexagonal system. The density of the h-BN material is 2.27g / cm 3The size of the h-BN material is 300-500 nm, and the nanographene powder is a two-dimensional material composed of a single layer of carbon atoms.
[0007] More preferably, the plasticizer is di(2-ethylhexyl) phthalate (DEHP) or diisononyl phthalate (DINP).
[0008] Further preferably, the stabilizer is a combination of lead, zinc, barium and oxygen.
[0009] Further preferably, the flame retardant is any one of organic phosphates, inorganic phosphates, halogen-containing compounds, metal oxides, nitrogen oxides, silicates, carbides, sulfides, borides and phosphides, or a combination of at least two thereof.
[0010] Further preferably, the filler concentration is controlled at 10wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 15 parts of MXene powder, 50 parts of h-BN material, 0.5 parts of nano-graphene powder, 70 parts of silica gel, polyimide and polyetheretherketone blend, 5 parts of urea, 1.5 parts of plasticizer, 1 part of stabilizer, and 1 part of flame retardant.
[0011] Further preferably, the filler concentration is controlled at 30wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 18 parts of MXene powder, 55 parts of h-BN material, 1 part of nano-graphene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 6 parts of urea, 2 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
[0012] Further preferably, the filler concentration is controlled at 50wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 20 parts of MXene powder, 60 parts of h-BN material, 2 parts of nano-graphene powder, 80 parts of silica gel, polyimide and polyetheretherketone blend, 8 parts of urea, 2.5 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
[0013] A method for preparing a high thermal conductivity electromagnetic shielding silica gel composite material comprises the following steps:
[0014] Step 1: Prepare raw materials by weighing MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend, urea, plasticizer, stabilizer and flame retardant according to the required proportions;
[0015] Step 2: Mixing and dispersing: Put MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend and urea into a stirrer or a ball mill for uniform mixing, and add plasticizer, stabilizer and flame retardant for uniform mixing;
[0016] Step 3: Forming and curing: pouring the evenly mixed composite material into a mold and curing it by heating or ultraviolet irradiation;
[0017] Step 4: post-processing, taking the cured high thermal conductivity electromagnetic shielding silicone composite material out of the mold, cutting and polishing it, and then cleaning and packaging the final product;
[0018] Step 5: Performance testing: conducting performance testing on the thermal conductivity and electromagnetic shielding effectiveness of the prepared high thermal conductivity electromagnetic shielding silicone composite material.
[0019] Further preferably, in step one, the symmetrically taken MXene powder is cleaned and dried for pretreatment, and the symmetrically taken nanographene powder is dispersed and ultrasonically pretreated.
[0020] Further preferably, in step 2, after uniform mixing using a stirrer or a ball mill, ultrasonic dispersion technology is used to break up the agglomeration between the powder particles so that the MXene powder and the nano-graphene powder are uniformly dispersed in the silica gel.
[0021] The embodiment of the present invention has the following advantages due to the adoption of the above technical solution:
[0022] 1. The present invention introduces MXene powder of two-dimensional transition metal carbide or nitride with excellent thermal conductivity as a thermal conductivity enhancing material, so that the thermal conductivity of the silica gel composite material is significantly improved, thereby enhancing the thermal conductivity of silica gel, improving the heat transfer efficiency, reducing the heat accumulation inside the equipment, and improving the performance and life of the equipment.
[0023] 2. The present invention improves the electromagnetic shielding performance of the silicone composite material by adding nano-graphene powder with excellent conductivity and electromagnetic shielding performance, which can effectively block the transmission of electromagnetic waves, reduce the leakage and interference of electromagnetic radiation, and provide a strong guarantee for the stable operation of electronic equipment.
[0024] 3. The present invention not only improves the thermal conductivity and electromagnetic shielding performance of the silicone composite material through a reasonable raw material ratio and preparation process, but also ensures the stability and reliability of the material, meets the high requirements of modern electronic equipment for thermal conductivity and electromagnetic shielding performance, thereby helping to improve the performance and stability of the equipment, reduce the failure rate, and extend the service life.
[0025] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a flowchart of the preparation process of the high thermal conductivity electromagnetic shielding silica gel composite material of the present invention;
[0028] Figure 2 This is a performance table diagram of the high thermal conductivity electromagnetic shielding silica gel composite material of the present invention. DETAILED DESCRIPTION
[0029] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0030] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0031] In the prior art, the thermal conductivity of silicone materials is low and the electromagnetic radiation shielding effect is poor, which makes it difficult to meet the requirements of modern electronic equipment for thermal conductivity and electromagnetic radiation shielding.
[0032] like Figure 1 As shown, an embodiment of the present invention provides a high thermal conductivity electromagnetic shielding silica gel composite material, including the following raw materials, in parts by weight: 15 to 20 parts of MXene powder, 45 to 60 parts of h-BN material, 0.5 to 2 parts of nanographene powder, 70 to 80 parts of silica gel, polyimide and polyetheretherketone blend, 3 to 8 parts of urea, 1 to 3 parts of plasticizer, 1 to 2 parts of stabilizer, and 1 to 2 parts of flame retardant. MXene powder is a two-dimensional layered material derived from transition metal carbon / nitrogen / carbonitride. The h-BN material is composed of two elements, boron (B) and nitrogen (N). Its chemical formula is BN, and its crystal structure is hexagonal. The density of the h-BN material is 2.27 g / cm 3 The size of h-BN material is 300-500nm, and nanographene powder is a two-dimensional material composed of a single layer of carbon atoms.
[0033] By adding a certain amount of MXene powder, h-BN material and nano-graphene powder into the blend of silica gel, polyimide and polyetheretherketone in proportion, the MXene powder has an ultra-high thermal conductivity and excellent mechanical properties, and its unique layered structure enables heat to be transferred quickly, significantly improving the thermal conductivity of the composite material. Nano-graphene powder has excellent electrical conductivity and electromagnetic shielding properties. The h-BN material has the functions of insulation, isolation of MXene and graphene nanosheets, and thermal conductivity. The addition of h-BN material can further enhance the thermal conductivity of the composite material and help maintain the electromagnetic shielding performance of the material, thereby improving the thermal conductivity and enhancing the electromagnetic radiation shielding effect.
[0034] In Example 1, the plasticizer is di(2-ethylhexyl) phthalate (DEHP) or diisononyl phthalate (DINP). The plasticizer is a colorless, transparent, oily, viscous liquid that is easily soluble in organic solvents. The plasticizer is mainly used to increase the flexibility and processability of the material.
[0035] In Example 1, the stabilizer is a combination of lead, zinc, barium and oxygen. The stabilizer slows down the reaction rate, maintains chemical balance, reduces surface tension, and prevents light, thermal or oxidative decomposition, which is beneficial to improving the stability of solutions, colloids, solids and other substances.
[0036] In the first embodiment, the flame retardant is any one or a combination of at least two of organic phosphates, inorganic phosphates, halogen-containing compounds, metal oxides, nitrogen oxides, silicates, carbides, sulfides, borides and phosphides, and the flame retardant can prevent the spread of flames.
[0037] In Example 1, the filler concentration is controlled at 10wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material are calculated by weight, including 15 parts of MXene powder, 50 parts of h-BN material, 1 part of nano-graphene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 4 parts of urea, 1.5 parts of plasticizer, 1 part of stabilizer, and 1 part of flame retardant.
[0038] In Example 1, the filler concentration is controlled at 30wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material are calculated by weight, including 18 parts of MXene powder, 55 parts of h-BN material, 2 parts of nanographene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 6 parts of urea, 2 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
[0039] In Example 1, the filler concentration is controlled at 50wt%, and the raw materials for preparing the high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material are calculated by weight, including 20 parts of MXene powder, 60 parts of h-BN material, 0.5 parts of nano-graphene powder, 80 parts of silica gel, polyimide and polyetheretherketone blend, 3 parts of urea, 2.5 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
[0040] Embodiment 1
[0041] In addition, the present invention also provides a method for preparing a high thermal conductivity electromagnetic shielding silica gel composite material, comprising the following steps:
[0042] Step 1: Prepare raw materials by weighing MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend, urea, plasticizer, stabilizer and flame retardant according to the required proportions;
[0043] Step 2: Mixing and dispersing: Put MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend and urea into a stirrer or a ball mill for uniform mixing, and add plasticizer, stabilizer and flame retardant for uniform mixing;
[0044] Step 3: molding and curing: pouring the uniformly mixed composite material of silicone, polyimide and polyetheretherketone into a mold, and curing and molding by heating or ultraviolet irradiation;
[0045] Step 4: post-processing, taking out the cured high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material from the mold, cutting and grinding it, and packaging the final product after cleaning;
[0046] Step 5: Performance testing: conducting performance testing on the thermal conductivity and electromagnetic shielding effectiveness of the prepared high thermal conductivity electromagnetic shielding silicone, polyimide and polyetheretherketone blend composite material.
[0047] In Example 1, in step 1, the symmetrically taken MXene powder is cleaned and dried for pretreatment, and the symmetrically taken nano-graphene powder is dispersed and ultrasonically pretreated. By cleaning and drying the MXene powder for pretreatment, it is ensured that its surface is clean and free of impurities. By dispersing and ultrasonically pretreating the nano-graphene powder, its dispersibility in the silica gel, polyimide and polyetheretherketone blend is improved.
[0048] In Example 1, in step 2, after uniform mixing using an agitator or a ball mill, ultrasonic dispersion technology is used to break the agglomeration between the powder particles, so that the MXene powder and nano-graphene powder are uniformly dispersed in the silica gel, polyimide and polyetheretherketone blend. Ultrasonic dispersion mainly relies on cavitation bubbles formed by ultrasound in the liquid. These cavitation bubbles achieve dispersion and refinement of particles and additives through the process of rapid growth and final collapse and rupture, so that the powder is better dispersed in the silica gel, polyimide and polyetheretherketone blend matrix, thereby improving the conductivity, mechanical properties and electromagnetic shielding properties of the composite material.
[0049] Embodiment 2
[0050] The filler concentration was controlled at 10 wt%. According to the formula, 15 parts of MXene powder, 50 parts of h-BN material, 1 part of nanographene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 4 parts of urea, 1.5 parts of plasticizer, 1 part of stabilizer, and 1 part of flame retardant were weighed. The MXene powder and nanographene powder were cleaned and ultrasonically dispersed. The silica gel, polyimide and polyetheretherketone blend and urea were evenly mixed. Then, the treated MXene A mixture of e powder, nano-graphene powder, silica gel, polyimide and polyetheretherketone blend and urea is put into a ball mill for ball milling mixing and dispersion treatment. After adding plasticizer, stabilizer and flame retardant and mixing evenly, the silica gel, polyimide and polyetheretherketone blend composite material is poured into a mold and cured by ultraviolet irradiation. After curing, demolding, cutting and polishing are performed to obtain a high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material sample A.
[0051] The composite material was tested using a thermal conductivity tester and an electromagnetic shielding effectiveness test system. The test showed that the thermal conductivity of sample A reached 0.8W / (m·K) and the electromagnetic shielding effectiveness reached 40dB.
[0052] Embodiment 3
[0053] The filler concentration was controlled at 30 wt%. According to the formula, 18 parts of MXene powder, 55 parts of h-BN material, 1 part of nanographene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 6 parts of urea, 2 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant were weighed. The MXene powder and nanographene powder were cleaned and ultrasonically dispersed. The silica gel, polyimide and polyetheretherketone blend and urea were evenly mixed. Then, the treated MXene powder was added. A mixture of ne powder, nano-graphene powder, silica gel, polyimide and polyetheretherketone blend and urea is put into a ball mill for ball milling mixing and dispersion treatment. After adding plasticizer, stabilizer and flame retardant and mixing evenly, the silica gel, polyimide and polyetheretherketone blend composite material is poured into a mold and cured by ultraviolet irradiation. After curing, demolding, cutting and polishing are performed to obtain a high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material sample B.
[0054] The composite material was tested using a thermal conductivity tester and an electromagnetic shielding effectiveness test system. The test showed that the thermal conductivity of sample B reached 1.1W / (m·K) and the electromagnetic shielding effectiveness reached 48dB.
[0055] Embodiment 4
[0056] The filler concentration was controlled at 50 wt %. According to the formula, 20 parts of MXene powder, 60 parts of h-BN material, 0.5 parts of nanographene powder, 80 parts of silica gel, polyimide and polyetheretherketone blend, 3 parts of urea, 2.5 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant were weighed. The MXene powder and nanographene powder were cleaned and ultrasonically dispersed. The silica gel, polyimide and polyetheretherketone blend and urea were evenly mixed. Then, the treated MXene powder and nanographene powder were mixed with urea. A mixture of Xene powder, nano-graphene powder, silica gel, polyimide and polyetheretherketone blend and urea is put into a ball mill for ball milling mixing and dispersion treatment. After adding plasticizer, stabilizer and flame retardant and mixing evenly, the silica gel, polyimide and polyetheretherketone blend composite material is poured into a mold and cured by ultraviolet irradiation. After curing, demolding, cutting and polishing are performed to obtain a high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material sample C.
[0057] like Figure 2 As shown, the composite material is tested by a thermal conductivity tester and an electromagnetic shielding effectiveness test system. After the test, the thermal conductivity of sample B reaches 1W / (m·K) and the electromagnetic shielding effectiveness reaches 45dB.
[0058] After testing, according to the test results of sample A, sample B and sample C, the present invention controls the concentration ratio of the filler at 50wt%, and the thermal conductivity and electromagnetic shielding performance of the high thermal conductivity electromagnetic shielding silica gel, polyimide and polyetheretherketone blend composite material are optimal.
[0059] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of various changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high thermal conductivity electromagnetic shielding silica gel composite material, characterized in that: The preparation raw materials include, by weight, 15 to 20 parts of MXene powder, 45 to 60 parts of h-BN material, 0.5 to 2 parts of nanographene powder, 70 to 80 parts of silica gel, polyimide and polyetheretherketone blend, 3 to 8 parts of urea, 1 to 3 parts of plasticizer, 1 to 2 parts of stabilizer, and 1 to 2 parts of flame retardant. The MXene powder is a two-dimensional layered material derived from transition metal carbon / nitrogen / carbonitride, the size of the h-BN material is 300 to 500 nm, and the nanographene powder is a two-dimensional material composed of a single layer of carbon atoms.
2. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The plasticizer is diester phthalate or diisononyl phthalate.
3. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The stabilizer is a combination of lead, zinc, barium and oxygen.
4. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The flame retardant is any one of organic phosphates, inorganic phosphates, halogen-containing compounds, metal oxides, nitrogen oxides, silicates, carbides, sulfides, borides and phosphides, or a combination of at least two thereof.
5. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The filler concentration is controlled at 10wt%. The raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 15 parts of MXene powder, 50 parts of h-BN material, 0.5 parts of nano-graphene powder, 70 parts of silica gel, polyimide and polyetheretherketone blend, 5 parts of urea, 1.5 parts of plasticizer, 1 part of stabilizer, and 1 part of flame retardant.
6. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The filler concentration is controlled at 30wt%. The raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 18 parts of MXene powder, 55 parts of h-BN material, 1 part of nanographene powder, 75 parts of silica gel, polyimide and polyetheretherketone blend, 6 parts of urea, 2 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
7. The high thermal conductivity electromagnetic shielding silica gel composite material according to claim 1, characterized in that: The filler concentration is controlled at 50wt%. The raw materials for preparing the high thermal conductivity electromagnetic shielding silicone composite material include, by weight, 20 parts of MXene powder, 60 parts of h-BN material, 2 parts of nano-graphene powder, 80 parts of silica gel, polyimide and polyetheretherketone blend, 8 parts of urea, 2.5 parts of plasticizer, 1.5 parts of stabilizer, and 1.5 parts of flame retardant.
8. A method for preparing a high thermal conductivity electromagnetic shielding silicone composite material, using the high thermal conductivity electromagnetic shielding silicone composite material as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Prepare raw materials by weighing MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend, urea, plasticizer, stabilizer and flame retardant according to the required proportions; Step 2: Mixing and dispersing: Put MXene powder, nanographene powder, silica gel, polyimide and polyetheretherketone blend and urea into a stirrer or a ball mill for uniform mixing, and add plasticizer, stabilizer and flame retardant for uniform mixing; Step 3: Forming and curing: pouring the evenly mixed composite material into a mold and curing it by heating or ultraviolet irradiation; Step 4: post-processing, taking the cured high thermal conductivity electromagnetic shielding silicone composite material out of the mold, cutting and polishing it, and then cleaning and packaging the final product; Step 5: Performance testing: conducting performance testing on the thermal conductivity and electromagnetic shielding effectiveness of the prepared high thermal conductivity electromagnetic shielding silicone composite material.
9. The method for preparing a high thermal conductivity electromagnetic shielding silica gel composite material according to claim 8, characterized in that: In step one, the symmetrically taken MXene powder is cleaned and dried for pretreatment, and the symmetrically taken nanographene powder is dispersed and ultrasonically pretreated.
10. The method for preparing a high thermal conductivity electromagnetic shielding silica gel composite material according to claim 8, characterized in that: In step 2, after uniform mixing using a stirrer or a ball mill, ultrasonic dispersion technology is used to break the agglomeration between the powder particles, so that the MXene powder and nanographene powder are uniformly dispersed in the silica gel, polyimide and polyetheretherketone blend.